Levitation Performance of Radial Film Riding Seals for Gas Turbine Engines - Syed Muntazir Mehdi; Young Cheol Kim; Eojin Kim (Lubricants)
Turbomachinery in gas turbines uses seals to control the leakage between regions of high and low pressure, consequently enhancing engine efficiency and performance. A film riding seal hybridizes the advantages of contact and non-contact seals, i.e., low leakage and low friction and wear. The literature focuses on the leakage performance of these seals; however, one of their fundamental characteristics, i.e., the gap between the rotor and seal surface, is scarcely presented. The seal pad levitates due to the deflection of the springs at its back under the influence of hydrodynamic forces. This study develops a test rig to measure the levitation of film riding seals. A high-speed motor rotates the rotor and gap sensors measure the levitation of the seal pads. Measurements are also compared with the predictions from a Reynolds equation-based theoretical model. Tests performed for the increasing rotor speed indicated that, initially, until a certain rotor speed, the pads adjust their position, then rub against the rotor until another rotor speed is reached, before finally starting levitating with further increased rotor speeds. Moreover, both the measured and predicted results show that pads levitated the most when located 90° clockwise from the positive horizontal axis (bottom of seal housing) compared to other circumferential positions.